Two Blades of Grass: The Impact of the Green Revolution - Gollin, Douglas; Hansen, Casper Worm; Wingender, Asger Mose (Journal of Political Economy, 2021)
We examine the economic impact of high-yielding crop varieties (HYVs) in developing countries 1960-2000. We use time variation in the development and diffusion of HYVs of 10 major crops, spatial variation in agro-climatically suitability for growing them, and a differences-in-differences strategy to identify the causal effects of adoption. In a sample of 84 counties, we estimate that a 10 percentage points increase in HYV adoption increases GDP per capita by about 15 percent. This effect is fully accounted for by the direct effect on crop yields, factor adjustment, and structural transformation. We also find that HYV adoption reduced both fertility and mortality.